Exploratory study of the level of depression in children and adolescents from 8 to 16 years old with child abuse in South Lima - Novoa Ramos, Paola del Carmen (2002)
A sample of 80; 8- to 16-year-old teenager children from both sexes, was selected for the study using the questionnaire for children depression (CDS). They were treated in the children abuse Office of Lima.